2024
DOI: 10.1021/acsomega.3c06826
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mechanism of Riboswitch to Natural Ligand Elucidated by McMD-Based Dynamic Docking Simulations

Gert-Jan Bekker,
Yoshifumi Fukunishi,
Junichi Higo
et al.

Abstract: Flavin mononucleotide riboswitches are common among many pathogenic bacteria and are therefore considered to be an attractive target for antibiotics development. The riboswitch binds riboflavin (RBF, also known as vitamin B 2 ), and although an experimental structure of their complex has been solved with the ligand bound deep inside the RNA molecule in a seemingly unreachable state, the binding mechanism between these molecules is not yet known. We have therefore used our Multicanonical Molecular Dynamics (McM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…Therefore, both the conformation of the β-switch, which is the difference between r 1 and r 12 , and the large number of configurations that have OS1 bound to the LRR motif (i.e., r 2 , r 3 , r 5 , r 7 , and r 11 ) must therefore influence binding and therefore be fundamental to the binding mechanism between the two molecules. In our previous work, we found that McMD-based dynamic docking simulations prefer “easy to attain” complexes, ,, i.e., those with a fast association followed by a slow transition to the native configuration, but that the validation stage of our pipeline gives a better understanding of the overall binding stability, i.e., it is more capable of identifying stable binding configurations with a slow dissociation. Therefore, further analysis might provide key insights into the kinetic properties of the binding configurations.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, both the conformation of the β-switch, which is the difference between r 1 and r 12 , and the large number of configurations that have OS1 bound to the LRR motif (i.e., r 2 , r 3 , r 5 , r 7 , and r 11 ) must therefore influence binding and therefore be fundamental to the binding mechanism between the two molecules. In our previous work, we found that McMD-based dynamic docking simulations prefer “easy to attain” complexes, ,, i.e., those with a fast association followed by a slow transition to the native configuration, but that the validation stage of our pipeline gives a better understanding of the overall binding stability, i.e., it is more capable of identifying stable binding configurations with a slow dissociation. Therefore, further analysis might provide key insights into the kinetic properties of the binding configurations.…”
Section: Resultsmentioning
confidence: 96%
“…Docking using molecular dynamics (MD) simulations, called dynamic docking, can be used to explore binding configurations between receptor proteins and their ligands . We have developed a dynamic docking implementation based on multicanonical molecular dynamics (McMD), , which we have applied to a number of cases from small-molecule ligands, medium-sized ligands, and peptides binding to protein receptors, as well as small-molecule ligand binding to an RNA riboswitch . In addition, we have applied McMD simulations (see Section S1 for an explanation of the McMD theory , ) to the conformational sampling of proteins and peptides and the loop structure prediction of an antibody .…”
Section: Introductionmentioning
confidence: 99%